2014
DOI: 10.4161/rna.29439
|View full text |Cite
|
Sign up to set email alerts
|

The importance of helix P1 stability for structural pre-organization and ligand binding affinity of the adenine riboswitch aptamer domain

Abstract: We report here an in-depth characterization of the aptamer domain of the transcriptional adenine-sensing riboswitch (pbuE) by NMR and fluorescence spectroscopy. By NMR studies, the structure of two aptamer sequences with different lengths of the helix P1, the central element involved in riboswitch conformational switching, was characterized. Hydrogen-bond interactions could be mapped at nucleotide resolution providing information about secondary and tertiary structure, structure homogeneity and dynamics. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
(67 reference statements)
1
31
2
Order By: Relevance
“…This again contrasts with a recent report suggesting that a pbuE riboswitch variant with an elongated P1 helix (9 bp stabilized with four additional G-C pairs) and stabilizing P1 have a negative impact on RNA folding and ligand affinity (32). We observed that the concentration of 2-AP in the growth medium required to elicit a half-maximal regulatory response was also very similar between the two RNAs (ϳ300 M for the wild type and ϳ100 M for (P1ϩ8),NUCL/GAAA), suggesting that P1 stability is not important for regulatory function.…”
Section: Volume 290 • Number 7 • February 13 2015contrasting
confidence: 99%
“…This again contrasts with a recent report suggesting that a pbuE riboswitch variant with an elongated P1 helix (9 bp stabilized with four additional G-C pairs) and stabilizing P1 have a negative impact on RNA folding and ligand affinity (32). We observed that the concentration of 2-AP in the growth medium required to elicit a half-maximal regulatory response was also very similar between the two RNAs (ϳ300 M for the wild type and ϳ100 M for (P1ϩ8),NUCL/GAAA), suggesting that P1 stability is not important for regulatory function.…”
Section: Volume 290 • Number 7 • February 13 2015contrasting
confidence: 99%
“…This difference in stemlength is conserved across tandem glycine riboswitches, with aptamer-1 always containing a 3-7 base P0 with an 8-9 base P1, while aptamer-2 has only a 5-6 base P1 helix Sherman et al 2012). Similar differences in P1 helix length and stability have been shown to cause pronounced differences in structure and ligand responsiveness for two adenine riboswitches (Nozinovic et al 2014).…”
Section: Discussionmentioning
confidence: 74%
“…Other riboswitches have been shown to use scaffolding to preform significant portions of the aptameric secondary structure prior to ligand binding, including prequeuosine class-II (Soulière et al 2013), S-adenosylmethionine (SAM)-I , SAM-II (Haller et al 2011), cyclic-di-guanosine monophosphate (c-di-GMP) (Wood et al 2012), and the purine riboswitches (Lemay et al 2006;Brenner et al 2010;Nozinovic et al 2014). Scaffolding can have important consequences for kinetically controlled riboswitches (Wickiser et al 2005a,b;Trausch and Batey 2014), allowing ligand binding to occur on transcriptionally relevant time scales.…”
Section: Discussionmentioning
confidence: 99%
“…In the holo-state, P1 is fully formed. Due to ligand-induced stabilization of helix P1 [42], formation of helix P4, which includes a long-range anti-SD/SD motif, is suppressed. Importantly, nucleotides A111 to U125 that contain the ribosome binding region (the Shine-Dalgarno sequence and the AUG-start codon) do not form base pairs and are therefore accessible to ribosome binding in the holo state.…”
Section: Multiple Stable Long-lived Conformations For Apo-states Of Rmentioning
confidence: 99%